Digital Leadership and Organizational Transformation: A Literature Review - Nuraini, Sri (Jurnal Ilmiah WUNY, 2025)
This article aims to systematically review literature related to the role of digital leadership in driving organizational transformation in the era of technological disruption. This research employs a literature review method by collecting and analyzing scientific articles from various indexed databases, such as Scopus, Web of Science, and Google Scholar, published between 2019-2024. The inclusion criteria encompass articles relevant to digital leadership and organizational transformation themes in both public and private sectors. The review findings indicate that digital leadership significantly contributes to the success of organizational transformation by strengthening digital vision, enhancing change management, and increasing innovation capacity. Digital leaders are required to possess competencies in technology, collaborative communication, and adaptive change management. However, digital leadership implementation also faces challenges such as organizational culture resistance, digital infrastructure limitations, and a lack of technological literacy at leadership levels. This study recommends the need for developing digital leadership models that align with local contexts and sectoral characteristics to comprehensively enhance digital transformation effectiveness.